The last twelve miles eaudiobook A novel. - Robuck, Erika (Tantor Media, 2024)
1926, Washington, DC In the Prohibition Rum Wars, the Coast Guard is losing. But the Coast Guard has a new, secret weapon. That secret weapon is a 5'2" mastermind in heels, who also happens to be a wife and mother: Mrs. Elizebeth Smith Friedman. Bahamas When Marie Waite notices discrepancies in cargo, she insists on accompanying her husband, Charlie, on a run. There, not only does Marie witness her husband's shortcomings, but she becomes enthralled by Cleo Lythgoe, "The Bahama Queen," who announces her retirement. Marie knows an opportunity when she sees it, and she wants the crown for herself so badly she can taste it. So begins Marie's plan to rise as rumrunner royalty long enough to get her family in the black. What she didn't count on was that the more sophisticated her operation grows, the more she comes on the radar of the feds, nabbing criminals by the daily dozen. Once Marie knows who she's up against, she's more determined than ever to triumph. On the other side of the law, Elizebeth is the only codebreaker battling scores of smugglers. Once the work becomes personal, and she discovers Marie as a premier adversary, Elizebeth's desire to catch the woman becomes almost obsessive.